Influence of marginal fit and cement types on microleakage of all-ceramic crown systems - Ece Yüksel; Ali Zaimoğlu (Sociedade Brasileira de Pesquisa Odontológica, 2011)
The purpose of this study was to evaluate the effects of both marginal fit and cementing with different luting agents on the microleakage of all-ceramic crown systems. Thirty-six extracted upper central incisors were prepared for full-coverage crowns and were divided into three groups. Group 1: CAD/CAM-fabricated ZrO2, Group 2: Heat-pressed lithium-disilicate, and Group 3: Cast Cr-Co copings as the control group. Copings were made following standard techniques, and groups were assigned cementation with either self-adhesive resin cement (A) or glass-ionomer luting cement (B). The specimens were subjected to thermocycling, immersed in basic fuchsin solution, sectioned mesiodistally and buccolingually. The surface of each section was digitally photographed under a stereomicroscope. Microleakage was scored using a five-point scale, and the marginal gap was measured using image analysis software. Data were statistically analyzed using 2-way ANOVA, Kruskal-Wallis, and Mann-Whitney U tests (α: 0.05). The marginal discrepancy of each group was 82.7 ± 7 µm, 92.6 ± 4 µm and 96.5 ± 7 µm respectively. Group 1 showed significantly smaller gaps than Group 3 (P = 0.042). Self-adhesive resin cement (A) showed a lower level of microleakage than glass-ionomer luting cement (B) in all groups (P = 0.029). Microleakage scores of '0' were 83% for 1A, 50% for 1B, 50% for 2A, 16% for 2B, 33% for 3A and none for 3B. Marginal discrepancy and cement type both had significant effects on microleakage. Lower levels of microleakage were recorded with self-adhesive resin cement, while CAD/CAM-fabricated ZrO2 copings showed smaller marginal discrepancy and less microleakage in comparison to cast Cr-Co.